2015
DOI: 10.1002/nha3.20098
|View full text |Cite
|
Sign up to set email alerts
|

Outing the Imposter: A Study Exploring Imposter Phenomenon among Higher Education Faculty

Abstract: Attention to faculty development, especially factors influencing faculty satisfaction and performance, has increased in the last decade. While a significant focus has been on contextual factors (i.e., tenure policies, mentoring, work‐life integration), fewer studies have examined individual psychological factors especially in the field of human resource development. This descriptive study addresses a particular focus in faculty development by examining the prevalence of faculty experiences of imposter phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 39 publications
4
84
0
2
Order By: Relevance
“…Finally, clear communication of the medical educator role, well‐defined expectations and organisationally appropriate boundaries are important to combating lingering feelings of insecurity around identity and legitimacy in both individuals and the medical education community . These should be coupled with the provision of targeted advice on the acquisition of skills, and structural support and time for personal development and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, clear communication of the medical educator role, well‐defined expectations and organisationally appropriate boundaries are important to combating lingering feelings of insecurity around identity and legitimacy in both individuals and the medical education community . These should be coupled with the provision of targeted advice on the acquisition of skills, and structural support and time for personal development and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, clear communication of the medical educator role, well-defined expectations and organisationally appropriate boundaries are important to combating lingering feelings of insecurity around identity and legitimacy in both individuals and the medical education community. 32,33 These should be coupled with the provision of targeted advice on the acquisition of skills, and structural support and time for personal development and practice. This has a twofold benefit in both supporting those who are in medical education roles and in providing an easily recognisable public face of the medical educator identity to permit better understanding among those who are not themselves educators.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our session came up with a variety of ideas such as mentorship, completing projects, setting goals, and developing relationships as markers for success. Hutchins and Rainbolt (2017) and Hutchins (2015) show that coping mechanisms such as social support (mentors for example), validation of successes, positive affirmations, and selftalk (for example, encouraging and motivating oneself using phrases or mantras to influence ones internal dialogue) are common features of coping mechanisms for IS in academic faculty and apply to the strategies found by our participants.…”
Section: Confronting Imposter Syndrome Through Guided Activitiesmentioning
confidence: 62%
“…Hutchins (2015) even found that higher rates of IS thoughts in academic faculty were tied to lower ratings in job performance. As was summarized by Hutchins and Rainbolt (2017) and Hutchins (2015), research finds that IS thoughts correlate with anxiety, burnout, psychological distress, fatigue, and emotional and cognitive distance from work, which again leads to poorer work outcomes in satisfaction and performance.…”
Section: Confronting Imposter Syndrome Through Guided Activitiesmentioning
confidence: 99%
See 1 more Smart Citation